Pengaruh Teori Behavioristik Terhadap Pembelajaran Sejarah Kebudayaan Islam (SKI) Di Kelas IX MTs. Nurussalam Delitua - Bobby Sultan Ali; Yurmaini Yurmaini; Mesran Mesran (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Behaviorism is one of the schools of psychology that studies individual behavior in relation to observable activities. This Behaviorist Theory is known as a learning theory, as all human behavior is considered the result of a learning process. Islamic Cultural History (Sejarah Kebudayaan Islam or SKI) is a subject that begins with the origins, development, and role of Islamic culture, as well as the history of pre-Islamic Arab society. It also explores figures who made significant contributions to Islamic history in the past, including the history of the birth and prophethood of the Prophet Muhammad (peace be upon him) up to the era of the Rightly Guided Caliphs (Khulafaurrashidun). This research is a quantitative descriptive study using the results of a mini research analysis. The study was conducted at MTs. Nurussalam Deli Tua, with a population consisting of all ninth-grade students (Class IX) totaling 224 students. This research used purposive sampling technique with a sample of 47 respondents. The independent variable is the behaviorist theory, and the dependent variable is the learning of Islamic Cultural History. The measuring tool used was a questionnaire consisting of 10 questions for the independent variable and 10 questions for the dependent variable. The results showed that the application of behaviorist theory in Class IX at MTs. Nurussalam Delitua was categorized as good with a percentage of 89.16%, while the learning of Islamic Cultural History was categorized as fairly good with a percentage of 73.62%. There is a significant influence of behaviorist theory on the learning of Islamic Cultural History with an F-value of 17.603, which is greater than the F-table value of 1.679. The influence of behaviorist theory on the learning of Islamic Cultural History is 28%.